Overlapping topics in advisory reports issued by five well-established European National Immunization Technical Advisory Groups from 2011 to 2014. Issue 50 (7th December 2016) - Nijsten, Daniëlle; Houweling, Hans; Durupt, Antoine; Adjagba, Alex
Abstract: National Immunization Technical Advisory Groups (NITAGs) are facing increasingly complex vaccination issues together with a lack of human resources for evidence assessment and data analysis. One way to reduce these burdens could be to share some of the preparatory work across NITAGs. We conducted an inventory of all the advisory reports issued by five well-established European NITAGs from 2011 to 2014 to assess overlaps in issues and activities. A total of 104 advisory reports were retrieved. Advisory reports on the same issues were compared to identify overlapping activities and processes. Advisory reports issued by the five NITAGs showed little overlap in issues and processes. A first step towards efficient collaboration would be to establish an independent platform to provide insight into each NITAG's work and to facilitate the exchange of agendas, assessment frameworks and evidence.